Evaluation of MTA insertion techniques in apically prepared teeth simulating incomplete root formation: an in vitro study (Research, Society and Development, 2022)
Apexification with MTA in incomplete rhizogenesis allows the formation of the apical barrier quickly and safely, however, there is difficulty in its insertion in the root canals. In this study, the efficacy of apical sealing in human teeth was comparatively evaluated in vitro, when the devices: MTA carrier, Lentulo spiral and gutta-percha cone were used. Sixty extracted anterior teeth were used, with lengths between 20 and 25 mm. The preparation of root canals was carried out by using Gates-Glidden drills, progressively, from number 1 to number 4, and for the simulation of apical divergence, the 5 was used, in a retrograde fashion. The sample was randomized into 3 groups (n=20) to make the apical plugs. Group 01, Lentulo, group 2, the MTA carrier and group 3, gutta-percha #80. The quality of the apical barriers was evaluated by a resident in Endodontics, through digital periapical radiographs. A score from 0 to 3 was considered, verifying the correspondence of the apical plug to the radiographic apex, the filling of the apical 4 mm of the root, and the absence of space between the material and the canal walls. The results showed that there was no significant difference between the groups (p> 0.05) and the scores in descending order were: 2 (48.3%), 1 (23.3%), 3 (18.4%) and 0 (10%). It was concluded that there was no difference in the effectiveness of apical sealing in human teeth, in vitro, simulating incomplete rhizogenesis, when compared to the Lentulo spiral, the MTA carrier, and gutta percha cone.